Probalusan: Integrating Problem-Based Learning with the Susan Loucks-Horsley Model for Contextual Science Learning - Rosaniya E. Rehiara (Journal of Education Research, 2026)
Contextual science learning requires a design that connects authentic problems, inquiry, evidence-based explanations, solutions, action, and reflection. This article formulates Probalusan as an integrative framework combining Problem-Based Learning with the Susan Loucks-Horsley model and explains its phases, mechanisms, assessment system, and validation agenda. An integrative narrative review synthesised literature on problem-based learning, inquiry, science process skills, formative assessment, socioscientific issues, and teacher professional development. Analysis involved pedagogical-function extraction, functional-equivalence mapping, consolidation of overlapping stages, and propositional synthesis. The resulting framework comprises five phases: Problem Orientation–Invitation, Learning Organisation–Exploration, Investigation–Explanation, Solution Development–Taking Action, and Presentation–Reflection–Evaluation. Probalusan establishes a coherent problem–evidence–action pathway, positions assessment as an evidence-and-decision system, and supports adaptation to local contexts. It provides a basis for instructional development and empirical research; however, construct validity, implementation fidelity, comparative effectiveness, and sustainability require multisite testing.